The effects of free oxygen radical scavenger and platelet-activating factor antagonist agents in experimental acute pancreatitis - HAKLAR, GONCAGÜL; YÜKSEL, MERAL (LIPPINCOTT WILLIAMS & WILKINS, 1999)
This study was done to evaluate the possible preventive effects of reactive oxygen species (ROS) scavenger agent desferrioxamine (DFX) and platelet-activating factor (PAF) antagonist agent: ginkgo biloba (GB) in an experimental acute pancreatitis model. Seventy-eight CD-1 mice were divided into six groups consisting of 10-13 mice. Induction of pancreatitis was achieved by cerulein injection in groups 2-5. The first group was control, whereas DFX and GB were used alone or in combinations as preventive agents in groups 3-5. DFX or GB were injected to the mice in groups 6 and 7 to evaluate any toxic effect. The assessment of the pancreatic edema and inflammation, the measurement of the amylase and the pancreatic weight and the measurement of the pancreatic tissue oxidative capacity by chemiluminescence method were the parameters to evaluate pancreatitis. Although the results indicate DFX and GB alone or in combinations have significant preventive roles, this was not a complete prevention.
Keywords: acute pancreatitis; desferrioxamine; reactive oxygen species; platelet-activating factor antagonist; MOUSE ACUTE-PANCREATITIS; SUPEROXIDE-DISMUTASE; EXPERIMENTAL-MODELS; SECRETORY PROTEINS; LIPID PEROXIDE; LUNG INJURY; RATS; ANTIOXIDANT; PATHOGENESIS; MACROPHAGES